Additively manufactured three-dimensional open-cell tubular-lattice structures for balanced mechanical behaviors. (15th March 2023) - Dong, Jianhua; Jing, Fengnian; Fan, Hualin
Highlights: An open-cell plate-lattice structure was designed and printed. Orthogonal tubular lattice structure has balanced strength and energy absorption. Local plate buckling controls the failure while global shear buckling is restrained. Abstract: Tubular structures usually have strong anisotropic mechanical behaviors. Based on ordinary tubular structure (OTS) with unidirectional tubes, a three dimensional tubular-lattice structure (TDTS) with orthogonal tubes was designed and fabricated by powder bed fusion method to balance the anisotropy in strength and energy absorption. Compression experimental results reveal that the printed TDTSs have balanced compressive and energy absorbing properties in three orthogonal directions, while the OTSs are sensitive to the loading direction. Arranging tubes in three orthogonal directions endows the TDTS balanced mechanical behaviors, effectively improved in [0 1 0] and [0 0 1] and slightly decreased in [1 0 0].